Mitigation of host cell mutations and regime shift during microbial fermentation: a perspective from flux memory. (December 2020) - Czajka, Jeffrey J; Okumuş, Burak; Koffas, Mattheos AG; Blenner, Mark; Tang, Yinjie J
Abstract : Microbial engineering forces flux redistribution to accommodate higher production rates, straining the cellular supply chain and leading to growth deficiency. Thus, there is a selective pressure to alleviate metabolic burden and revert towards the innate flux distribution ('flux memory') via mutations. Suboptimal fermentation exacerbates this phenomenon as increased number of generations prolong the selection window for the underlying flux memory to generate faster growing non-producers. New strategies to mitigate host genetic instability include laboratory evolution, high-resolution genome resequencing combined with phenotype screening, mismatch repair protein engineering, and advanced synthetic biology approaches (e.g. oscillators and biosensor regulators). Moreover, 13 C-metabolic flux analysis can quantify flux suboptimality driven by metabolic burdens and cultivation stresses. Elucidation of correlations between metabolic suboptimality and host mutation rates/spectra may lead to early stage risk assessments of culture-population's regime shift during process scale-up as well as strategies to boost bioproductions.